Estimating DEA efficiency using uniform distribution - Hossain, Md. Kamrul; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (Universiti Sains Malaysia, 2014)
The most commonly used non-parametric tool for measuring the relative efficiency of Decision Making Units (DMU) is Data Envelopment Analysis (DEA). In this article, a method for measuring the efficiency level of a DMU when it is in an unfavourable situation as well as estimating the efficiency using uniform distribution is shown. The efficiency score from the traditional BCC-DEA model and the efficiency score in an unfavourable situation form an interval.This interval, known as interval efficiency, is used to estimate efficiency using uniform distribution.In an empirical example, a 95 percent confidence interval (CI) is calculated for the efficiency score using a three-point estimation method.The analysis indicated that the efficiencies that were estimated from uniform distribution are all within the confidence interval. In addition, a statistical test shows that there is no significant different between the estimated efficiency and the efficiency from DEA.